Annulment of Arbitral Awards as an Instance of Procedural Abuse - Rigel, Budiman; Soermartono, Gatot P (Jurnal Ilmu Hukum Kyadiren, 2026)
Arbitration is a dispute resolution mechanism that guarantees finality and legal certainty for business actors. However, in practice, the annulment mechanism regulated under Article 70 of Law Number 30 of 1999 is often misused by the losing party to delay or evade the enforcement of an arbitral award. This research employs a normative juridical method with a conceptual and statutory approach to analyze how such misuse constitutes an abuse of process. The findings indicate that bad-faith annulment practices undermine the principle of finality, reduce public trust in arbitration, and create legal uncertainty. Therefore, a restrictive interpretation of annulment provisions and a stronger application of the principle of good faith are necessary to prevent procedural abuse within Indonesia’s arbitration system.